English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-12 03:08:40 · 6 answers · asked by og 1 in Science & Mathematics Mathematics

6 answers

4(2c-d=-2)
4(4c+d=20)
=========
8c-4d=-8
16c+4d=80
=========
24c=72
c=3
4(3)+d=20
12+d=20
d=8
(3,8)

2(3)-8=-2
6-8=-2
-2=-2

4(3)+8=20
12+8=20
20=20

2006-12-12 16:13:40 · answer #1 · answered by Anonymous · 4 1

(1) 2c-d=-2
(2) 4c+d=20

rearrange (2) to d=20-4c; then sub into (1) to get 2c-(20-4c)=-2, call this equation (3)

expand (3) to get 2c-20+4c=-2; simplify to get 6c=18. Therefore c=3

sub c=3 into (1) to get 2(3)-d=-2 & simplify to get 6-d=-2
therefore d=8

check (2) by using c=3 & d=8: 4(3)+8=20; 12+8=20

2006-12-12 03:25:11 · answer #2 · answered by azfong 2 · 3 0

2c-d=-2 equation(1)
4c+d=20 equation(2)
by adding the two equations
6c=18
c=3
d=8

2006-12-12 07:34:55 · answer #3 · answered by mira 2 · 3 1

I know how to do this, but it is kind of hard to explain. c= -9 and d= 56. I am guessing that is right. For the 4c+d=20 you just subtract 4c from both sides. So you would get d=20-4c. then you just plug that into the first equation to get c. then when you get c you plug it into 20-4c.

2006-12-12 03:18:25 · answer #4 · answered by Math Geek 2 · 1 3

2c - d = 24c + d = 20

2c - d - 2c = 24c + d = 2c = 20

- d = 22c + d = 20

- d + d = 22c + d + d = 20

0 = 22c + 2d = 20

22c + 2d = 20

2(11c + d) = 20

- - - - - -s-

2006-12-12 04:12:10 · answer #5 · answered by SAMUEL D 7 · 3 1

adding
6c=18
dividing by 6
c=3
substituting in 2c-d=-2
2(3)-d=-2
ading -6
-d=-8
so d=8
solution set{3,8}

2006-12-12 03:21:54 · answer #6 · answered by raj 7 · 3 1

fedest.com, questions and answers